Megakaryocyte gene targeting mediated by restricted expression of recombinase Cre - Nowakowski, Adam; Alonso-Martín, Sonia; Arias-Salgado, Elena G.; Fernández, Darío; Vilar, MariPaz; Ayuso, Matilde S.; Parrilla, Roberto (Thrombosis and Haemostasis, 2011)
The availability of mice with tissue-specific expression of recombinase Cre is the limiting step for a successful gene targeting by the Cre-LoxP methodology. This work aimed at generating transgenic mice with restricted expression of recombinase Cre in megakaryocytes and platelets, driven by the promoter of the αIIb gene (mαIIb-cre). Mice oocytes were microinjected with a 4.1 Kb construct comprising a 2.7 Kb promoter fragment of the glycoprotein αIIb gene, linked to the CrecDNA and followed by the polyA tail of the SV40. We found four mice with positive DNA genotype and three probable sites of genomic integration of the transgene. Only two of the founders showed presence of Cre-mRNA and production of Cre protein, restricted to megakaryocytes. The activity of Cre in mediating gene targeting was assessed by crossing mαIIb-cre mice to Cre-reporter mice (ROSA26-lacZ). The activity of β-galactosidase, detected only in megakaryocytes, was sufficient to generate intense staining of X-Gal in hepatic haematopoietic islands of 14.5 dpc fetuses, in bone marrow megakaryocytes and platelets from adult mice as well as in vitro cultured megakaryocytes differentiated from bone marrow hematopoietic stem cells. Moreover, the recombinase activity was sufficient to produce the specific gene targeting of a floxed CD40L allele in megakaryocytes. The mαIIb-cre transgenic mice with restricted production of Cre in megakaryocytes, offers a selective, alternative, new tool for the genetic analysis of platelet pathophysiology.
Keywords: Tissue-specific transgenesis; Cre in megakaryocytes; Cre-loxP; gene targeting mediated by Cre